Aronia melanocarpa L. fruit peels show anti-cancer effects in preclinical models of breast carcinoma: The perspectives in the chemoprevention and therapy modulation - Dvorska, Dana; Mazurakova, Alena; Lackova, Lenka; Sebova, Dominika; Kajo, Karol; Samec, Marek; Brany, Dusan; Svajdlenka, Emil; Treml, Jakub; Mersakova, Sandra; Strnadel, Jan; Adamkov, Marian; et al. (Frontiers in Oncology, 2024)
IntroductionWithin oncology research, there is a high effort for new approaches to prevent and treat cancer as a life-threatening disease. Specific plant species that adapt to harsh conditions may possess unique properties that may be utilized in the management of cancer.HypothesisChokeberry fruit is rich in secondary metabolites with anti-cancer activities potentially useful in cancer prevention and treatment.Aims of the study and MethodsBased on mentioned hypothesis, the main goal of our study was to evaluate the antitumor effects of dietary administered Aronia melanocarpa L. fruit peels (in two concentrations of 0.3 and 3% [w/w]) in the therapeutic syngeneic 4T1 mouse adenocarcinoma model, the chemopreventive model of chemically induced mammary carcinogenesis in rats, a cell antioxidant assay, and robust in vitro analyses using MCF-7 and MDA-MB-231 cancer cells.ResultsThe dominant metabolites in the A. melanocarpa fruit peel extract tested were phenolic derivatives classified as anthocyanins and procyanidins. In a therapeutic model, aronia significantly reduced the volume of 4T1 tumors at both higher and lower doses. In the same tumors, we noted a significant dose-dependent decrease in the mitotic activity index compared to the control. In the chemopreventive model, the expression of Bax was significantly increased by aronia at both doses. Additionally, aronia decreased Bcl-2 and VEGF levels, increasing the Bax/Bcl-2 ratio compared to the control group. The cytoplasmic expression of caspase-3 was significantly enhanced when aronia was administered at a higher dosage, in contrast to both the control group and the aronia group treated with a lower dosage. Furthermore, the higher dosage of aronia exhibited a significant reduction in the expression of the tumor stem cell marker CD133 compared to the control group. In addition, the examination of aronia`s epigenetic impact on tumor tissue through in vivo analyses revealed significant alterations in histone chemical modifications, specifically H3K4m3 and H3K9m3, miRNAs expression (miR155, miR210, and miR34a) and methylation status of tumor suppressor genes (PTEN and TIMP3). In vitro studies utilizing a methanolic extract of A.melanocarpa demonstrated significant anti-cancer properties in the MCF-7 and MDA-MB-231 cell lines. Various analyses, including Resazurin, cell cycle, annexin V/PI, caspase-3/7, Bcl-2, PARP, and mitochondrial membrane potential, were conducted in this regard. Additionally, the aronia extract enhanced the responsiveness to epirubicin in both cancer cell lines.ConclusionThis study is the first to analyze the antitumor effect of A. melanocarpa in selected models of experimental breast carcinoma in vivo and in vitro. The utilization of the antitumor effects of aronia in clinical practice is still minimal and requires precise and long-term clinical evaluations. Individualized cancer-type profiling and patient stratification are crucial for effectively implementing plant nutraceuticals within targeted anti-cancer strategies in clinical oncology.